Glycosmis kanburiensis: A new species of Rutaceae from Thailand - Wichai Aiyakool; Srunya Vajrodaya (Sigmul bunryu hag-hoeji = Korean journal of plant taxonomy, 2023)
Glycosmis kanburiensis (Rutaceae) from Kanchanaburi Province, southwestern Thailand is described as a new species. It is similar to G. esquirolii (H. Lév.) Tanaka in its dendriform habit, terminal inflorescences, and large leaflets, but several easily recognizable differences in floral features, including triangular sepals with rust-colored indumentum (vs. broadly ovate villose sepals), globose, glabrous (vs. subglobose, villosus) ovary, cylindrical and attenuate (vs. stout) style, and ellipsoid (vs. globose) fruit. A taxonomic description, illustration, photographs, geographical distribution, ecological data, and conservation status are provided.